2006
DOI: 10.1152/japplphysiol.01336.2005
|View full text |Cite
|
Sign up to set email alerts
|

Exercise-induced reversal of insulin resistance in obese elderly is associated with reduced visceral fat

Abstract: Exercise improves glucose metabolism and delays the onset and/or reverses insulin resistance in the elderly by an unknown mechanism. In the present study, we examined the effects of exercise training on glucose metabolism, abdominal adiposity, and adipocytokines in obese elderly. Sixteen obese men and women (age = 63 +/- 1 yr, body mass index = 33.2 +/- 1.4 kg/m2) participated in a 12-wk supervised exercise program (5 days/wk, 60 min/day, treadmill/cycle ergometry at 85% of heart rate maximum). Visceral fat (V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
173
3
7

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 201 publications
(194 citation statements)
references
References 45 publications
(50 reference statements)
11
173
3
7
Order By: Relevance
“…Several studies have investigated the effect of exercise on adiponectin concentration in humans. Although some studies found that the concentration of circulating adiponectin increased after exercise (Lim et al, 2008;Kondo et al, 2006), in other studies, the concentration of circulating adiponectin was unchanged after exercise (Jürimäe et al, 2007;O'Leary et al, 2006;Klimcakova et al, 2006;Nassis et al, 2005;Hara et al, 2005). Likewise, some studies have reported that the concentration of circulating adiponectin in healthy and diabetic rodents increased after exercise (Zeng et al, 2007;Lee et al, 2011), whereas in other studies, the concentration of circulating adiponectin in healthy rodents was unchanged after exercise (Lee et al, 2011;Bhattacharya et al, 2005;Huang et al, 2007).…”
Section: Exercise Alters Adipokine Secretionmentioning
confidence: 98%
“…Several studies have investigated the effect of exercise on adiponectin concentration in humans. Although some studies found that the concentration of circulating adiponectin increased after exercise (Lim et al, 2008;Kondo et al, 2006), in other studies, the concentration of circulating adiponectin was unchanged after exercise (Jürimäe et al, 2007;O'Leary et al, 2006;Klimcakova et al, 2006;Nassis et al, 2005;Hara et al, 2005). Likewise, some studies have reported that the concentration of circulating adiponectin in healthy and diabetic rodents increased after exercise (Zeng et al, 2007;Lee et al, 2011), whereas in other studies, the concentration of circulating adiponectin in healthy rodents was unchanged after exercise (Lee et al, 2011;Bhattacharya et al, 2005;Huang et al, 2007).…”
Section: Exercise Alters Adipokine Secretionmentioning
confidence: 98%
“…et al demonstrated an exercise training-induced reduction in visceral fat, 9 abdominal subcutaneous fat, and total abdominal fat. In these studies, the volunteers exercised at ~70% of VO 2max , 5 days of week for 50-60 minutes and lost ~7 pounds over the course of the study.…”
Section: Peak Oxygen Consumption and Maximum Work Outputmentioning
confidence: 97%
“…8 In addition, O'Leary et al demonstrated a relationship between exercise training-induced reductions in visceral fat and improvements in glucose metabolism. 9 However, the optimal intensity of exercise necessary to promote the reduction of visceral fat has not been evaluated in elderly, obese adults.…”
Section: Introductionmentioning
confidence: 99%
“…Total fat and fat free mass were measured using the intelligence dual X-ray absorptiometry system (iDXA; Lunar Prodigy, Madison, WI), and visceral adipose tissue mass was determined using computerized tomography (CT) as previously described. 15 In brief, subjects were placed in a supine position, and measurements were made at 120 kV with a slice thickness of 8 mm. Images were obtained manually without contrast at the fourth lumbar vertebra (L 4 ).…”
Section: Anthropometrics and Fitnessmentioning
confidence: 99%